2022
DOI: 10.1021/acsaem.2c00534
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of Li-Added Mo–Nb Oxide as the Anode for Li-Ion Batteries with N-Carbon Coating

Abstract: High capacity, fast charging/discharging, safe operation, and long cycle-time are the essential properties of lithium-ion batteries (LiBs) for electric vehicles and large-scale energy storage applications. To meet those properties, an alternative anode has to be developed to replace the traditional graphite electrode. This study aims to demonstrate the effectiveness of Mo–Nb oxide (MNO)-based anode material for fast charging LiB. LiOH is primarily used not only as a source of Li dopant but also as a sintering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…78-886. The crystal properties of NSF- n were further investigated by the XRD Rietveld refinement technique according to our recent study, and the results are shown in Figure S1 and Table . It can be clearly seen from Table that the lattice parameters ( a and c ) and the cell volume expand after the addition of FeCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…78-886. The crystal properties of NSF- n were further investigated by the XRD Rietveld refinement technique according to our recent study, and the results are shown in Figure S1 and Table . It can be clearly seen from Table that the lattice parameters ( a and c ) and the cell volume expand after the addition of FeCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has demonstrated improving the cyclability and capacity retention of Si nanoparticles (Si-NPs) by covering them with nanometer-thick coating layers. The function of the coating layer, meanwhile, is far from apparent from the perspectives of surface chemistry and electrochemical-mechanical impact. Recently, the lithiation/delithiation kinetics of Si-NPs covered with the conductive polymer polypyrrole were examined using in situ transmission electron microscopy (PPy) .…”
Section: In Situ/operando Characterizations Of Si Anodementioning
confidence: 99%
“…The key is to explore materials with continuous crystal structures for excellent conductivity, open host lattices for fast Li + diffusion, and suitable lithiation potentials (41.0 V vs. Li + /Li) for adequate safety. Combined with the above requirements, titanium-based oxides (such as Li 4 Ti 5 O 12 , 8,9 TiO 2 10 ) and niobium-based oxides (such as Nb 2 O 5 , 6,11,12 Ti/Nb oxides, [13][14][15][16][17][18][19] Mo/Nb oxides, 20,21 and W/Nb 1,5,[22][23][24][25][26] ) have been considered as promising candidates for high-rate anodes at the micrometer scale. The operating voltage (1.0-2.0 V vs. Li + /Li) of these materials limits the formation of lithium dendrite and SEI film even at very high rate, simultaneously suppresses the degradation of electrolyte, which results in a good security performance.…”
Section: Introductionmentioning
confidence: 99%